Glycosphingolipids and lysosomal storage disorders as illustrated by gaucher disease. (December 2019) - Aerts, Johannes M.F.G.; Kuo, Chi-Lin; Lelieveld, Lindsey T.; Boer, Daphne E.C.; van der Lienden, Martijn J.C.; Overkleeft, Herman S.; Artola, Marta
Abstract: Glycosphingolipids are important building blocks of the outer leaflet of the cell membrane. They are continuously recycled, involving fragmentation inside lysosomes by glycosidases. Inherited defects in degradation cause lysosomal glycosphingolipid storage disorders. The relatively common glycosphingolipidosis Gaucher disease is highlighted here to discuss new insights in the molecular basis and pathophysiology of glycosphingolipidoses reached by fundamental research increasingly using chemical biology tools. We discuss improvements in the detection of glycosphingolipid metabolites by mass spectrometry and review new developments in laboratory diagnosis and disease monitoring as well as therapeutic interventions. Highlights: Glycosphingolipids are structural components of the cell membrane. Impaired degradation causes lysosomal glycosphingolipid storage disorders. Chemical biology tools are presently used in fundamental research and diagnosis. Diagnosis has been markedly improved by sensitive quantitation of glycosphingolipids. Therapeutic intervention may profit from new insights in pathophysiology.